Discourse on the Application of Dwangsom on Execution Court Decisions: A Comparison with Netherlands and France - Khaliza Fauzi, Maghfira Nur; Erliyana, Anna (Fakultas Hukum Universitas Lampung, 2024)
The classic problem in resolving State Administration disputes boils down to the process of implementing decisions by the parties, which in practice still does not fully meet the expectations of justice seekers. If the decision is not implemented, the State Administrative Court (PTUN) imposes administrative sanctions / coercive measures against the losing party, which can be in the form of sanctions for forced payment of money (dwangsom), in order to increase the executable power of the decision. Normally, the same as the General Court, even though currently there are not many cases, it is still a problem. Article 116 paragraph (4) of the PTUN Law regulates the mechanism for coercive measures against the execution of PTUN decisions, but it is still interpreted as containing a